PTU-155 Progression Of Low Grade Dysplasia To High Grade Dysplasia In Barrett's Oesophagus In A Single Centre. (9th June 2014) - Clark, L-L; Richardson, G; Paterson, S
Abstract : Introduction: Barrett's oesophagus is a common condition found in 4% of patients undergoing upper gastrointestinal endoscopy. (1) The association between Barrett's oesophagus and oesophageal adenocarcinoma has been well established. Scotland has a particularly high incidence of both Barrett's and adenocarcinoma of the oesophagus. The risk of progression from high grade dysplasia (HGD) to oesophageal adenocarcinoma (OAC) has been reported at approximately 10% per year. 1 However the risk of progression from low grade dysplasia (LGD) is harder to quantify with studies showing progression to OAC from 0.6–1.69% per year, not dissimilar to that of non-dysplasic Barrett's. 2 More recently the SURF trail reported a 25% (17/68) progression from LGD to HGD/OAC in a surveillance group with LGD versus radiofrequency ablation. 3 Methods: In 2009 a clinical database of Barrett's patients was developed in Forth Valley Hospital to ensure appropriate surveillance as per BSG guidelines. All patients diagnosed with Barrett's were cared for by one responsible team, a dedicated Barrett's endoscopy list was developed, and the use of narrow band imaging was introduced. At the end of 2012 the database was interrogated to assess the progress of all patients who had been diagnosed with LGD within the previous three years. Results: There were 915 patients with Barrett's on the database, of which 829 were under follow up. 85 (10%) had LGD and of this patient cohort 19 had progressed to HGD. The progression rate from LGD to HGD was 22% (19/85). The median follow up of patients with LGD was 29 months (range 12–34 months). All patients who progressed from LGD to HGD had endoscopic therapy with endoscopic mucosal resection and /or ablative therapies. There are no recorded cases of progression of LGD to OAC. Conclusion: The progression rate from LGD to HGD is similar to reported rates found in the SURF trial. This suggests that LGD carries a greater risk of progression, and therefore worse prognosis than previously reported. This is a potential group of patients in whom to consider early intervention rather than adopt the standard surveillance strategy. Further studies to evaluate the effectiveness of treatment rather than surveillance in this group should be considered. References: Consensus Statements for Management of Barrett's Dysplasia and Early-Stage Esophageal Adenocarcinoma, Based on a Delphi Process. Gastroenterology 2012;143 (2):336–346 Sachin W, Sharad M. How to manage a Barrett's Esophagus patient with low grade dysplasia. Clin Gastroenterol Hepatol . 2009;7(1):27–32 Phoa K, von Vilstern, F. Radiofrequency Ablation in Barrett's esophagus with confirmed low-Grade dysplaisa: interm results of a European multipcentre randomized controlled trial (SURF). Gastroenterology 2013: 5 Supplement1 S187 Disclosure of Interest: None Declared.